The Authority of Internal Auditor to Prevent Corruption Committed by Civil Servants and Government Official - Helmi Helmi; Iskandar Iskandar (Faculty of Law, Jambi University, 2019)
Internal audit is significant to guarantee and ensure the enforcement of laws and regulations as well as to prevent power abuse by civil servants or government officials that may cause financial loss for the country. The purpose of this study is to provide an overview of the authority of internal audit, to describe how this authority is regulated, to depict the authority to prevent power abuse, and to illustrate the protection over and enforcement of administrative law on allegation of power abuse. This study is a normative juridical study analyzing primary and secondary legal material relevant to the subject under study. The result of the study reveals that the authority of internal audit has been set in various legal products. The operating procedures for legal protection over allegation of arbitrary behavior against civil servants or government officials are filing an objection or an appeal against the discovery of the internal audit. If the case is not a subject of investigation of law enforcement officers the accused may contest the finding to Administrative Court and request the judge to review the finding. If the accused is proven to be guilty of abusing power that causes financial loss for the state and, thus, be sentenced for the alleged conduct (inkracht), he or she shall be immediately dismissed from his/her position. The regulation posits that officer who ignores the verdict and continues to keep the defendant on his/her position shall be penalized.